Menyeimbangkan Akal dan Hati: Integrasi Psikologi Kognitif dan Humanistik dalam Pembelajaran - Nufus Tahfidzi; Siti Rohati; Hunainah; Fandy Adpen Lazzavietamsi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article explores the significant roles of cognitive and humanistic psychology in the learning process. Cognitive psychology emphasizes how learners process information, construct knowledge, and develop critical thinking skills through mental stages described by theorists such as Piaget, Bruner, and Gagné. Meanwhile, humanistic psychology focuses on the holistic development of human potential by placing needs, intrinsic motivation, and self-actualization at the core of education. Using a library research approach, this study finds that both theories complement each other: cognitive psychology enhances learners’ intellectual abilities, while humanistic psychology nurtures emotional and social growth. The integration of both approaches leads to a more meaningful, effective, and human-centered learning process, where teachers act as facilitators who help students understand themselves and their surroundings.